خريطة البحوث العلمية في الألعاب اللغوية لتدريس اللغة العربية - Adrizal, Salmi (Maharaat Lughawiyyat: Jurnal Pendidikan Bahasa Arab, 2025)
This research aims to identify bibliometric data and conduct a critical reflection on studies related to the use of language games as a medium for Arabic language learning. It also aims to determine which titles have high novelty value to serve as a reference for researchers in publishing future scientific works. The researcher employs a library research approach using the Systematic Literature Review method. Data collection was conducted using the Publish or Perish (POP) software, Crossref, and analysis was carried out using the VOSviewer application. The data search was based on the keyword "Arabic Language Games" in two languages, Indonesian and Arabic, within the time range of 2019–2023. An analysis of 259 published articles using the VOSviewer application through co-occurrence produced bibliometric visualizations based on keywords, including network visualization, overlay visualization, and density visualization. The findings revealed that pantomime games, digital games, bingo games, Kahoot games, and games using AI have high novelty value and potential for further research. Keywords: language games, AI-based games, title mapping